The conspiracy to end America : five ways my old party is driving our democracy to autocracy - Stevens, Stuart (Twelve, 2023)
Today's Republican party has become an autocratic movement masquerading as a political party. If we turn our backs on that truth, we greatly increase the likelihood that the America we love will slip away, never to return. Whenever a democracy slides into autocracy, there are five critical elements at work: financiers, propagandists, support of a major party, legal theories to legitimize authoritarian acts, and shock troops. The book examines each of these driving forces on the Right and makes clear how they are working in concert to end our democracy as we know it.